The geology of the Målingen structure: A probable doublet to the Lockne marine‐target impact crater, central Sweden. (4th March 2014) - Ormö, J.; Sturkell, E.; Nõlvak, J.; Melero‐Asensio, I.; Frisk, Å.; Wikström, T.
Abstract The Målingen structure is an approximately 700 m wide, rimmed, sediment‐filled, circular depression in Precambrian crystalline basement approximately 16.2 km from the concentric, marine‐target Lockne crater (inner, basement crater diameter approximately 7.5 km, total diameter in sedimentary strata approximately 13.5 km). We present here results from geologic mapping, a 148.8 m deep core drilling from the center of the structure, detailed biostratigraphic dating of the structure's formation and its age correlation with Lockne, chemostratigraphy of the sedimentary infill, and indication for shock metamorphism in quartz from breccias below the crater infill. The drill core reveals, from bottom to the top, approximately 33 m of basement rocks with increased fracturing upward, approximately 10 m of polymict crystalline breccia with shock features, approximately 97 m of slumped Cambrian mudstone, approximately 4.7 m of a normally graded, polymict sedimentary breccia that in its uppermost part grades into sandstone and siltstone (cf. resurge deposits), and approximately 1.6 m of secular sediments. The combined data set shows that the Målingen structure formed in conjunction with the Lockne crater in the same marine setting. The shape and depth of the basement crater and the cored sequence of crystalline breccias with shocked quartz, slumped sediments, and resurge deposits support an impact origin. The stratigraphic and geographic relationship with Lockne suggests the Lockne and Målingen craters to be the first described doublet impact structure by a binary asteroid into a marine‐target setting.